Accelerating Community Welfare: A Study of Public Perceptions of the Role of Zakat Management Organizations (OPZ) - Widi Nopiardo; Emrizal (ZAWA: Management of Zakat and Waqf Journal, 2025)
Zakat is a fiscal instrument aimed at sustainable social welfare. Accelerating the improvement of the welfare of those who mustahik is a crucial indicator of the success of zakat management. Although zakat funds collected continue to increase annually, studies show that poverty and dependency levels remain persistent issues. Theoretically, distribution through Zakat Management Organizations (OPZ) provides added value in the form of accelerating the welfare of those who mustahik through productive programs and mentoring. However, the community does not yet fully understand the importance of paying zakat through OPZ. This study used field research with a qualitative approach. Primary data were collected through in-depth interviews with selected muzaki (payers of zakat). The results showed that the majority of muzaki believed or had a positive perception that paying zakat through OPZ would accelerate the improvement of the welfare of those who mustahik.